Development of Sunflower (Helianthus annuus L.) with Application of Quail Manure under Different Irrigation Sheets (2020)
Alternatives are currently being sought to reduce the costs of fertilizers in agriculture. The application of organic matter is proposed not only as an alternative to improve the chemical properties of the soil but also as a mean to promote its physical properties and its ability to retain moisture. Quail manure is a resource rarely used in agriculture, which nowadays, due to its lack of use, is being wasted, thus becoming an important rural pollutant. The research was carried out to evaluate the effect of two doses (6250 y 12500 kg/ha) of quail manure per plant and two irrigation sheets (100 mL and 200 mL) on sunflower (Helianthus annuus L.) development through vegetative variables such as the height of the plants, the number of leaves, number of flower buds and flowering plants, variables which are evaluated every eight days. The experiment was established in Medellín city, a region characterized by its floricultural vocation, while the quail manure was obtained from a quail farm in the municipality of Marinilla, located in western Colombia. The treatments did not show significant differences for the variables related to the phenology of the plants, however, they showed a marked tendency for the 6250 kg/ha treatment in the improvement of the vegetative variables and in the weight of the seeds, in addition, the levels of quail manure used in the study did not show nutritional restriction effects in the plants for any of the variables measured.